Analisis Kinerja Pegawai Dalam Memberikan Pelayanan Administrasi Kepada Masyarakat Di Desa Semangat Dalam Handil Bakti Kabupaten Barito Kuala - Devia Hetty Hernany; Budi Setiawati; M. Agus Humaidi; Amelia Puspita (Journal on Education, 2024)
Performance can be known and measured if an individual or group of employees or employees have criteria or benchmark success standards set by the organization. Performance can also be said to be the product of doing something related to a job, position or role in an organization with a maximum sense of responsibility, dedication and loyalty. The performance referred to in this research is all the power and efforts made by employees in providing administrative services to the community. This expected performance is reflected in three aspects, namely, (a) the cognitive aspect, namely the employee's understanding of the administrative service system to the community,(b) the effective aspect, namely the performance of employees in service, is the efforts made by employees to accept and create harmonious interpersonal relationships with the community, (c) the performance aspect is everything that employees do in using their physical bodies in acting so that they can provide good service. best for society